Studi Peristiwa Masa Awal Pandemi Covid-19 dan Prediksi Analisis Teknikal Saham Perbankan Indonesia - Elizabeth Lucky Maretha; Franciscus Xaverius Hendra Prasetya (Jurnal Pasar Modal dan Bisnis, 2021)
The aim of the study was to examine events that occurred at the start of the Covid-19 pandemic and estimate the banking sector shares with technical analysis. The method used is a different test for each event, at the time of the first announcement of the Covid-19 pandemic in Indonesia, until the enactment of Large-Scale Social Restrictions (PSBB) for the first time in effect in Jakarta as the capital of Indonesia. As a result, when the Covid-19 pandemic was announced on Friday afternoon, it had an impact on trade transactions on Monday and Tuesday. This incident also caused a decline in stock trading, so that halt trading was imposed due to a decline in the JCI by more than five percent. The halt trading event itself has an impact on trading the following day. Whereas the Jakarta PSBB incident took place for the first time, the results had an impact for the first day as well as several days after the PSBB was implemented. Prediction of technical analysis shows that there is investor confidence after the government carries out fiscal and monetary policies for all companies that have an impact due to the Covid-19 pandemic. The banking sector estimate for November 2020, in the short term, has increased.